Energy and carbohydrate for training and recovery - Burke, L. M.; Loucks, A. B.; Broad, N. (Journal of Sports Sciences, 2006)
Soccer players should achieve an energy intake that provides sufficient carbohydrate to fuel the training and competition programme, supplies all nutrient requirements, and allows manipulation of energy or nutrient balance to achieve changes in lean body mass, body fat or growth. Although the traditional culture of soccer has focused on carbohydrate intake for immediate match preparation, top players should adapt their carbohydrate intake on a daily basis to ensure adequate fuel for training and recovery between matches. For players with a mobile playing style, there is sound evidence that dietary programmes that restore and even super-compensate muscle glycogen levels can enhance activity patterns during matches. This will presumably also benefit intensive training, such as twice daily practices. As well as achieving a total intake of carbohydrate commensurate with fuel needs, the everyday diet should promote strategic intake of carbohydrate and protein before and after key training sessions to optimize the adaptations and enhance recovery. The achievement of the ideal physique for soccer is a long-term goal that should be undertaken over successive years, and particularly during the off-season and pre-season. An increase in lean body mass or a decrease in body fat is the product of a targeted training and eating programme. Consultation with a sports nutrition expert can assist soccer players to manipulate energy and nutrient intake to meet such goals. Players should be warned against the accidental or deliberate mismatch of energy intake and energy expenditure, such that energy availability (intake minus the cost of exercise) falls below 125 kJ (30 kcal) per kilogram of fat-free mass per day. Such low energy availability causes disturbances to hormonal, metabolic, and immune function.